Lad, a dog : best dog in the world best dog in the world - Lundell, Margo; Terhune, Albert Payson, 1872-1942.; Bolognese, Don (New York : Scholastic Inc., 1997)
Whisked away from his country estate to compete in a dog show in New York City, Lad is confused and unhappy and wishes only to go home.
"Cartwheel books."
Keywords: Dogs -- Fiction; Dogs -- Juvenile fiction; Dog shows -- Fiction; New York (N.Y.) -- Fiction